2001
DOI: 10.1385/cbb:34:2:257
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Pteridine Nucleoside Analogs: A Window on DNA Interactions

Abstract: Pteridine nucleoside analog probes are highly fluorescent and offer different approaches to monitor subtle DNA interactions with other molecules. Similarities in structure and size to native nucleosides make it possible to incorporate these probes into oligonucleotides through the standard deoxyribose linkage. These probes are formulated as phosphoramidites and incorporated into oligonucleotides using automated DNA synthesis. Their position within the oligonucleotide renders them exquisitely sensitive to chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
111
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(117 citation statements)
references
References 37 publications
6
111
0
Order By: Relevance
“…A recently developed group of fluorescent base analogues are the pteridines (for recent review see Hawkins) 20 . Of the available pteridines the two guanine analogs 3-methylisoxanthopterine (3-MI) and 6-methylisoxanthopterine (6-MI) have been synthesized as phosphoramidites and incorporated into DNA oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…A recently developed group of fluorescent base analogues are the pteridines (for recent review see Hawkins) 20 . Of the available pteridines the two guanine analogs 3-methylisoxanthopterine (3-MI) and 6-methylisoxanthopterine (6-MI) have been synthesized as phosphoramidites and incorporated into DNA oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…Hawkins and co-workers have described substituted pteridines as fluorescent analogues of DNA bases (see ref 8 for review), and they have identified 3-methylisoxanthopterin (3MI) and 6-methylisoxanthopterin (6MI) as two particularly promising guanine analogues. Both analogues have absorbance bands that are at lower energies (red-shifted) than those of the naturally occurring nucleic acids and amino acids, allowing selective excitation of the analogues.…”
Section: Introductionmentioning
confidence: 99%
“…We have used the available high resolution structures of UP1 to incorporate the fluorescent guanosine analog 6-methyl-8-(2-deoxy-␤-ribofuranosyl)isoxanthopteridine (6-MI) into the oligonucleotide d(TTAGGG) 2 as a probe for studying UP1 interactions to hTR DNA (33,34). Previous fluorescence studies using either the quenching of intrinsic tryptophan fluorescence or the fluorescent nucleotide riboethanoadenylic acid have shown that UP1 binds promiscuously to single-stranded nucleic acids as part of its in vivo role in RNA processing and transport (22,23,27).…”
mentioning
confidence: 99%